Plant and animal-derived fusion nanovesicles rescue inflammation-compromised osteogenic potential of periodontal ligament stem cells - Lin, Jingxiong; Li, Manchun; Wang, Linglu; Lu, Xingyu; Xu, Quanle; Chen, Hongbo; Dai, Dongling (Frontiers in Cell and Developmental Biology, 2025)
Periodontitis is a chronic inflammatory disease affecting the supporting tissues of the teeth and has emerged as a global public health issue. Current therapies primarily address pathogenic factors and alleviate symptoms, with limited options available for complete restoration and reconstruction of already absorbed periodontal bone tissue. In this study, we developed a nanotherapeutic strategy utilizing fusion nanovesicles (FVs) to modulate the inflammatory microenvironment and create a regenerative niche for periodontal ligament stem cells (PDLSCs), which play a crucial role in periodontal tissue repair. The FVs are composed of Scutellaria baicalensis nanovesicles (SBNVs) with anti-Porphyromonas gingivalis (P. gingivalis) and anti-inflammatory properties, combined with PDLSC membrane-derived nanovesicles genetically engineered to express TNFR1. These FVs preserved the biological activity of SBNVs and the immunomodulatory function of PDLSCs. Additionally, FVs effectively captured and cleared TNF-α from the microenvironment through TNFR1. Moreover, FVs alleviated the inflammatory response of PDLSCs induced by P. gingivalis-LPS (Pg-LPS) and TNF-α, restoring their proliferation, migration, and osteogenic differentiation capabilities. Hence, this nanotherapeutic strategy holds great potential for treating periodontitis.